ASSOCIATION OF BORDA'S METHOD AND ANALYTIC HIERARCHY PROCESS (AHP) FOR THE ACQUISITION OF HELICOPTERS BY THE BRAZILIAN NAVY - Cruz, Eduardo Picanço; Fontanillas, Carlos Navarro; Possoli, Karen; Rodriguez Y Rodriguez, Martius Vicente (Revista Gestão da Produção Operações e Sistemas, 2020)
Purpose – To suggest using a combination of the Analytic Hierarchy Process (AHP) and the Borda Method for collective decision-making. By harmonizing cardinal scales from the results of the AHP and the Borda Method, the assessment of alternatives for new helicopters should maximize individual opinions when forming collective decisions. Design/methodology/approach – Qualitative and quantitative. Agents were interviewed who were involved in the process of acquiring Small Utility Helicopters for the Brazilian Navy. This included ten pilots and six military engineers from the Bureau of Aeronautics in the Brazilian Navy in Rio de Janeiro. Data were treated by combining cardinal scales from the AHP with the method proposed by Borda. Findings – By analyzing the MGPs taken from the AHP, it was found that judgment inconsistencies do not significantly affect the result. Both methods can promote helpful decision aids for the Brazilian Navy when deciding which aircraft to purchase to replace and improve the naval aviation fleet. Both methods can also be applied to similar situations in decision making between mutually exclusive alternatives. Originality/value – The use of hybrid decision aids (the result of combining methods) in a multicriteria analysis helps organizations make the best use of available resources, especially in complex decision scenarios. This study can help managers analyze limits more accurately for decisions to be accepted. Keywords - Collective decisions; Multicriteria; the Borda Method; Analytic Hierarchy Process.